2022
DOI: 10.1002/jimd.12580
|View full text |Cite
|
Sign up to set email alerts
|

Addition of galactose‐1‐phosphate measurement enhances newborn screening for classical galactosemia

Abstract: Galactosemia is an inborn disorder of carbohydrate metabolism of which early detection can prevent severe illness. Although the assay for galactose‐1‐phosphate uridyltransferase (GALT) enzyme activity has been available since the 1960s, many issues prevented it from becoming universal. In order to develop the Israeli newborn screening pilot algorithm for galactosemia, flow injection analysis tandem mass spectrometry measurement of galactose‐1‐phosphate in archived dried blood spots from newborns with classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…To develop a NBS pilot algorithm for galactosemia, archived dried bloodspots from newborns with GALT, galactosemia variants, and normal controls were analyzed by MS/MS for galactose-1-phosphate (Gal-1-P) by FIA MS/MS. Based on a successful pilot, a screening algorithm with Gal-1-P as the first-tier screening test, and GALT enzyme activity as the second-tier to identify newborns suspected to be at risk for classical galactosemia has been implemented [ 1349 ]. Another FIA MS/MS study demonstrated the feasibility of screening newborns for CTX, a progressive metabolic leukodystrophy, using two-tier screening with FIA MS/MS and LC MS/MS [ 1350 ].…”
Section: Resultsmentioning
confidence: 99%
“…To develop a NBS pilot algorithm for galactosemia, archived dried bloodspots from newborns with GALT, galactosemia variants, and normal controls were analyzed by MS/MS for galactose-1-phosphate (Gal-1-P) by FIA MS/MS. Based on a successful pilot, a screening algorithm with Gal-1-P as the first-tier screening test, and GALT enzyme activity as the second-tier to identify newborns suspected to be at risk for classical galactosemia has been implemented [ 1349 ]. Another FIA MS/MS study demonstrated the feasibility of screening newborns for CTX, a progressive metabolic leukodystrophy, using two-tier screening with FIA MS/MS and LC MS/MS [ 1350 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we routinely re-screen cases after fully oral feeding to decrease the possibility of false negative. Alternatively, assessing markers such as Gal-1-P [ 40 , 41 ] instead of TGal could be advantageous in accurately detecting elevated Gal-1-P levels in newborns. However, a caveat exists: patients with GALK deficiency may present with normal Gal-1-P levels or TGal and might be overlooked in such screenings.…”
Section: Discussionmentioning
confidence: 99%